To evaluate the given expression \(\frac{{[1 - (-4)^3]^2}}{{5^2 - 2.6}}\), we need to simplify both the numerator and denominator and then divide them.
First, let's simplify the numerator:
\([1 - (-4)^3]^2\)
= \([1 - (-64)]^2\) (since \((-4)^3 = -64\))
= \([1 + 64]^2\)
= \([65]^2\)
= \(65^2\)
= 4225
Now, let's simplify the denominator:
\(5^2 - 2.6\)
= \(25 - 2.6\)
= \(22.4\)
Finally, let's divide the simplified numerator by the simplified denominator:
\(\frac{{4225}}{{22.4}}\)
The rounded answer is approximately 188.6160714.
Therefore, your answer of 25 is not correct.
Algebra 1 9th grade evaluate the following expression (fraction) [1 - (-4)^3]^2 numerator the denominator is [5^2 - 2.6] I want to know if my answer is correct 25
1 answer